Cooling System in Machine Operation at Gas Engine Power Plant at PT Multidaya Prima Elektrindo - Syahrul Ghufron; Soni Prayogi (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2023)
In this work, it is reported that the development of technology makes the need for electrical energy in recent years has increased very rapid. PT Multidaya Prima Elektrindo is a company engaged in power generation using gas energy sources, namely the Gas Engine Power Plant. with a capacity of 2x6 MW. The energy produced by this plant will later be distributed to consumers through the State Electricity Company. Along with its use, generating machines continuously work for long periods of time. If this continues, there will be overheating of the engine which can cause a trip to the engine, to prevent a trip on the engine, monitoring the cooling system on the engine can prevent overheating which can cause a trip on the engine. By using a cooling system, the performance of the engine at the generator in generating energy is optimal. The processed data is weather data around the PLTG location and characteristic data from the gas turbine. The results of data processing are taken into consideration in choosing a cooling system. Other processing data in the form of cooling load is then used to design the components of the cooling system that will be applied. The results of the study show that reducing the outside air temperature entering the gas turbine compressor to 22 °C, can increase the output power of the PLTG gas turbine by more than 10 MW.